TFAP2A drives non-small cell lung cancer (NSCLC) progression and resistance to targeted therapy by facilitating the ESR2-mediated MAPK pathway - Ding-Guo Wang; Jian Gao; Jing Wang; Kun-Chao Li; Zhi-Bo Wu; Zhong-Min Liao; Yong-Bing Wu (Cell Death Discovery)
Abstract Cancer is among the leading causes of death related diseases worldwide, and lung cancer has the highest mortality rate in the world. Transcription factors (TFs) constitute a class of structurally and functionally intricate proteins. Aberrant expression or functional deficiencies of transcription factors may give rise to abnormal gene expression, contributing to various diseases, including tumours. In this study, we propose to elucidate the potential role and mechanism of TFAP2A in NSCLC. We found that TFAP2A levels were significantly greater in tumour tissues than para-tumour tissues, and high expression of TFAP2A was associated with poor prognosis in NSCLC patients. Additionally, TFAP2A overexpression promoted NSCLC progression both in vivo and in vitro. Mechanistically, ESR2 is a potential target regulated by TFAP2A and that TFAP2A can bind to the promoter region of ESR2. Furthermore, the overexpression of both TFAP2A and ESR2 in NSCLC cells was associated with the overactivation of MAPK signalling, and the combination of PHTPP and osimertinib had a synergistic effect on suppressing tumour growth.